2007
DOI: 10.1063/1.2756838
|View full text |Cite
|
Sign up to set email alerts
|

Self-diffusion of reversibly aggregating spheres

Abstract: Reversible diffusion limited cluster aggregation of hard spheres with rigid bonds was simulated and the self diffusion coefficient was determined for equilibrated systems. The effect of increasing attraction strength was determined for systems at different volume fractions and different interaction ranges. It was found that the slowing down of the diffusion coefficient due to crowding is decoupled from that due to cluster formation. The diffusion coefficient could be calculated from the cluster size distributi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…clusters are arrested by nearby clusters and thus only the dynamics within the cage is described. The long time limit (region III) also shows linear behavior that is due to crowding effects37. A similar transition from the ballistic regime of individual proteins to region I is also observed but not shown in this plot.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…clusters are arrested by nearby clusters and thus only the dynamics within the cage is described. The long time limit (region III) also shows linear behavior that is due to crowding effects37. A similar transition from the ballistic regime of individual proteins to region I is also observed but not shown in this plot.…”
Section: Resultssupporting
confidence: 61%
“…In such systems, one expects oligomerization and dissociation events, as well as a reduction of mobility due to oligomerization, crowding, or even dynamically arrested states37. In general, large bubbles induced by TFAM oligomerization are expected to contribute more to DNA compaction than small hinges.…”
Section: Resultsmentioning
confidence: 99%
“…Spheres that are part of the network are immobile until the bonds that tie them to the network are broken. A detailed study of the diffusion coefficient of square well fluids forming rigid bonds using BCD2 has been reported recently 30 . It was shown that D decreases with increasing B att following a power law for large B att and only becomes zero when the bonds are irreversible, i.e.…”
Section: Fig 4: Comparison Of the Mean Square Displacement Of Nonintmentioning
confidence: 99%
“…20,37,38,46 Accordingly, z * = P × z represents the bond coordination number, and ⟨z * ⟩ = P × ⟨z⟩ represents the average bond coordination number of the system. By adding up the number of bond clusters of size s, we get the distribution of bond cluster size n * (s).…”
Section: Cluster and Coordination Numbermentioning
confidence: 99%
“…9,14,20,[33][34][35][36][37][38][39] In our study, due to its advantages in dealing with discretized potentials, the event-driven MD 40 is employed to determine the loci of PTs for two types of percolation (namely, contact percolation and bond percolation, see Sec. II) and to investigate the structural properties of the colloidal system.…”
Section: Introductionmentioning
confidence: 99%